2016
DOI: 10.1016/j.bpj.2015.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Principles Governing the Self-Assembly of Coiled-Coil Protein Nanoparticles

Abstract: Self-assembly refers to the spontaneous organization of individual building blocks into higher order structures. It occurs in biological systems such as spherical viruses, which utilize icosahedral symmetry as a guiding principle for the assembly of coat proteins into a capsid shell. In this study, we characterize the self-assembling protein nanoparticle (SAPN) system, which was inspired by such viruses. To facilitate self-assembly, monomeric building blocks have been designed to contain two oligomerization do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…The concept of self-assembly Self-assembly is defined as the ability of some molecules to spontaneously arrange themselves into well-ordered structures (Whitesides and Grzybowski, 2002). In nature, this common phenomenon results in the production of a variety of ensembles using finite building blocks (Indelicato et al, 2016;Whitesides and Grzybowski, 2002). Natural self-assembled molecules are primarily composed of DNA, polypeptides, and proteins and are found in a wide variety of living organisms, such as virus capsids, cell membranes, enzymes, and the cellular cytoskeleton.…”
Section: Self-assembled Peptide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of self-assembly Self-assembly is defined as the ability of some molecules to spontaneously arrange themselves into well-ordered structures (Whitesides and Grzybowski, 2002). In nature, this common phenomenon results in the production of a variety of ensembles using finite building blocks (Indelicato et al, 2016;Whitesides and Grzybowski, 2002). Natural self-assembled molecules are primarily composed of DNA, polypeptides, and proteins and are found in a wide variety of living organisms, such as virus capsids, cell membranes, enzymes, and the cellular cytoskeleton.…”
Section: Self-assembled Peptide Nanoparticlesmentioning
confidence: 99%
“…In chemical methods, the building blocks sequences and buffer conditions may affect the molecular weight of the produced SAPN and its polymorphism (Indelicato et al, 2016). The nanoscale assembly is based on a fundamental parameter: the peptide solution concentration.…”
Section: General Considerations In Sapn Generationmentioning
confidence: 99%
“…SAPNs are rationally designed repetitive antigen displays that can function for a diverse array of antigens. Disease antigens can be added to either the C or the N terminus of each SAPN monomer, and in the prototypical SAPN 60 monomers will self-assemble into a particle with regular symmetry [187][188][189][190]. Each assembled SAPN is decorated on its surface with 60 copies of an antigen, making them excellent repetitive antigen displays (Fig.…”
Section: Rationally Designed Protein Nanovaccinesmentioning
confidence: 99%
“…In a standard icosahedral structure four LCMs can further self-assemble into a full SAPN structure, meaning that 60 monomers make up each SAPN. However, recent biophysical studies combined with an analysis using viral tiling theory has shown that the SAPNs can possibly also assemble into higher order assemblies containing multiples of 60 chains per particle [27]. Each SAPN is predicted to contain 60 copies (or a multiple thereof ) of P27A and P27-NC epitopes (Fig.…”
Section: Sapn Designmentioning
confidence: 99%